Digital communication: Priorities in the relationship of principal leadership and collaborative community at malaysian school - Yusof, Mat Rahimi; Syariff M. Fuad, Dayang Rafidah; Mohd Yaakob, Mohd Faiz; Don, Yahya; Ibrahim, Ibrahim (Horizon Research Publishing, 2020)
The impact of the development of the Industrial Revolution 4.0 (IR 4.0) also involved the communication element. This new medium of communication has taken its place recently in the most community to create a virtual community. Therefore, this quantitative study of 202 respondents was carried out to identify the contribution of this new medium of digital communication in the relationship between principal leadership and collaborative community in schools. The data were collected through the questionnaire and analysed using AMOS software version 22. It was found that principal's leadership contributed significantly to digital communication (β = .073, CR = 6.393, P = .000), the new medium of digital communication also contributed significantly to the collaborative community (β = .149, CR = 7.787, P = .000), and its' also contributed as a mediator between principals leadership and community at schools. These findings indicate that the relationship between school principals and collaborative community can be enhanced by the use of a new medium of digital communication such as WhatsApp, Telegram and any other methods. Through this study, a model of collaborative community measurement was developed. This model can be used as a guidance for all the principals to apply this medium in school and also provides a clear signal for the school leaders to achieve the ninth shift of Malaysia Education Blueprint (PPPM 2013-2025) that is a collaboration with parents, communities and the private sector as a whole.